Do Homo Oeconomicus ao Homo Vitium: uma arqueogenealogia do sujeito viciado na contemporaneidade - Prestes, Túlio Kércio Arruda (2022)
This work intended to carry out an archeogenealogy of the subject addicted to contemporaneity. In this way, we seek to understand how addiction, which was an issue linked to practical philosophy, when thematizing vices and virtues, becomes during the 19th to 21st centuries a medical problem, redefined in terms of addictive disorders. Thus, three starting questions animated this research: how was the experience of addiction constituted in contemporary times and how was drug use configured as an experience of addiction? What are the government mechanisms organized around the government of vices? How is the subject objectified as endowed with vices in contemporary times? The general objective is to investigate how an experience of addiction is constituted in modern and contemporary Western societies, so that individuals can and should recognize themselves as subjects of addictions, at the same time that a dispersed field is formed. of knowledge ranging from economics to neurosciences that deal with addictions based on economic/hedonistic calculations. By analyzing how addictive behaviors are explained between economic knowledge and medical knowledge, we can see the formation of an empirical-transcendental double in relation to addictions, which we call anthropological torpor. Anthropological torpor is, therefore, the objectification of man through both the narrative that links him to certain forms of addiction throughout history and the description of the subject in terms of an addicted constitution, linked to the mesolimbic dopaminergic pathways of addiction and of the reward. Therefore, the apparent paradox of our research problem resides in the analysis of how this heterogeneous group of knowledge constitutes vice/addiction as something a priori constituent of the human being, linked to his own nature (transcendental domain) and that attacks his nature, and to the at the same time resulting from historical and cultural ways of living individual and collective life (empirical domain) and that attacks the customs of a people. If Kant claimed to have awakened from dogmatic sleep thanks to Hume, while Foucault invited us to awaken from anthropological sleep, in this more humbly work we decided to simply accept Foucault's invitation to also awaken from the anthropological torpor contained in anthropological sleep, shedding light on about the modes of subjectivation from an addicted constitution of man. In the meantime, we analyze how the intelligibility grid of Homo oeconomicus is increasingly being applied to the field of neurosciences, enabling the construction of the functioning of the addicted/addicted organism, which calculates and acts with a view to obtaining an objective that is mediated by the reward pleasure. If Homo oeconomicus is what makes it possible for us to analyze drug policies and even addictions based on economic calculations, the neurosciences lean on Homooeconomicus to constitute a transcendental domain that encodes our relationship with life and with ourselves by calculating the reward. Homo vitium is the potentialization and molecularization of economic rationality to the pathways for the release of neurotransmitters, which encode our relationship with the world and with ourselves based on reward.